Proximity‐Induced Magnetism Enhancement Emerged in Chiral Magnet MnSi/Topological Insulator Bi2Se3 Bilayer. Issue 2 (16th December 2020) - Choi, Won‐Young; Jeon, Jae Ho; Bang, Hyun‐Woo; Yoo, Woosuk; Jerng, Sahng‐Kyoon; Chun, Seung‐Hyun; Lee, Sunghun; Jung, Myung‐Hwa
Abstract: A proximity effect between magnetic materials and topological surface states can generate and modulate the localized spins without complicated material structures, but its origin is not clearly verified. MnSi single layer and MnSi/Bi2 Se3 bilayer on Al2 O3 (001) substrates are fabricated by magnetron co‐sputtering and molecular beam epitaxy systems, in which a large proximity effect between the chiral magnetic structure and the topological surface states is manifested. The magnetic and electronic properties of both samples are meticulously compared and the proximity‐induced magnetism enhancement in the MnSi/Bi2 Se3 bilayer is found. Interestingly, this effect persists up to temperatures above 300 K. Furthermore, for the MnSi/Bi2 Se3 bilayer, the increase of charge carrier density and the decrease of carrier mobility near the Curie temperature T C = 40 K are observed, which can mediate the ferromagnetic exchange interaction enhancing the magnetization. The finding provides insight into a new platform to consist of materials with distinct topological phases for future spintronic devices. Abstract : The bilayer of MnSi and Bi2 Se3 leads to a large magnetism enhancement even though Bi2 Se3 is a diamagnetic material. This is attributed to the magnetic proximity effect between the chiral magnetic structure and the topological surface states. The finding provides an insight into new platform to consist of the materials with distinct topological phases for future spintronic devices.